Deficiency of HTRA2/Omi is associated with infantile neurodegeneration and 3-methylglutaconic aciduria. Issue 10 (12th May 2016) - Mandel, Hanna; Saita, Shotaro; Edvardson, Simon; Jalas, Chaim; Shaag, Avraham; Goldsher, Dorit; Vlodavsky, Euvgeni; Langer, Thomas; Elpeleg, Orly
Abstract : Background: Cell survival critically depends on the integrity of mitochondria, which play a pivotal role during apoptosis. Extensive mitochondrial damage promotes release of pro-apoptotic factors from the intermembrane space of mitochondria. Released mitochondrial proteins include Smac/DIABLO and HTRA2/Omi, which inhibit the cytosolic E3 ubiquitin ligase XIAP and other inhibitors of apoptosis proteins. Aims: Here we investigated the cause of extreme hypertonia at birth, alternating with hypotonia, with the subsequent appearance of extrapyramidal symptoms, lack of psychomotor development, microcephaly, intractable seizures and early death in four patients from two unrelated families. The patients showed lactic acidemia, 3-methylglutaconic aciduria, intermittent neutropenia, evolving brain atrophy and disturbed cristae structure in muscle mitochondria. Methods and results: Using whole-exome sequencing, we identified missplicing mutation and a 5 bp deletion in HTRA2, encoding HTRA2/Omi. This protein was completely absent from the patients' fibroblasts, whose growth was impaired and which were hypersensitive to apoptosis. Expression of HtrA2/Omi or of the proteolytically inactive HTRA2/Omi protein restored the cells' apoptotic resistance. However, cell growth was only restored by the proteolytically active protein. Conclusions: This is the first report of recessive deleterious mutations in HTRA2 in human. The clinical phenotype, the increased apoptotic susceptibility and the impaired cell growth recapitulate those observed in the Htra2 knockout mice and in mutant mice with proteolytically inactive HTRA2/Omi. Together, they underscore the importance of both chaperone and proteolytic activities of HTRA2/Omi for balanced apoptosis sensitivity and for brain development. Absence of HTRA2/Omi is associated with severe neurodegenerative disorder of infancy, abnormal mitochondria, 3-methylglutaconic aciduria and increased sensitivity to apoptosis.